A Phenomenological Study of Individual Strategies for Rebuilding Food Production Ability in Resource Poor Post-Conflict Farming Communities in Myanmar - Joshua Jason Ringer; Jeff Sallee; Robert Terry Jr.; Nicholas Brown; Craig E. Watters; Samantha Blackwell (Journal of International Agricultural and Extension Education, 2021)
The impact of armed conflict on small-holder agricultural production recently became a closely studied topic (Verwimp, 2011). In post-conflict, or perpetual low intensity conflict, situations policy makers have identified agricultural rehabilitation of small-holder food production as vital for preventing economic collapse, encouraging internally displaced persons (IDPs) to return totheir rural communities, and to reintegrate former insurgents into viable rural livelihoods (Christoplos, Longley, & Slaymaker, 2004). This issue has been studied at the regional and country level, but few studies have looked at this issue from resource poor small-holder farmers’ perspective (Shinn, 2010; Verwimp, Justino, & Bruck, 2007). This qualitative study documented the experience of resource-poor farmers who experienced armed conflict in northern Shan State, Myanmar. Thirty-four resource-poor farmers and six agricultural advisors were interviewed using semi-structured interview methods. The study was conducted over a three-month period in 2013. The study revealed eight themes, which described the reality of the post-conflict environment and small-holder strategies to cope and recover food production capacity. The themes were, armed conflict is always with the farmers; loss of animals and seed stock; loss of local markets; forest as refuge; fear of government and militias was mitigated by family networks; large agribusiness control land and employment; prolonged conflict causes movement to safe areas and neighboring countries; rebuilding food production. These findings reveal the need for policy makers and agricultural advisory services to modify their assistance strategies and services to better match upland resource-poor farmers realities and adaptation strategies.
Keywords: post-conflict; resource-poor; farmers; extension